Improving Cognitive Function of the Elderly through Tai Chi Exercise Program and Cognitive Stimulation - Riasmini, Ni Made; Sabri, Rika; Khatimah, Husnul; Resnayati, Yeti; Mulyana, Nana; Riyanti, Eska; Riyanto, Riyanto (Jurnal Keperawatan, 2024)
The increasing proportion of elderly followed by the increasing life expectancy has improved the prevalence of various chronic-degenerative diseases and dementia. The promotive efforts using exercise programs, such as Tai Chi and cognitive therapy, significantly increase the physical fitness, mental well-being, and cognitive function of the elderly. This research aimed to predict the effectiveness of exercise programs for particular groups living in nursing homes. The method of this research was a quasi-experiment with a control group design. Samples are elderly living in the nursing home. The research samples were 116 elderlies living in nursing homes in Jakarta and South Sumatra. They were selected using a random sampling strategy. Statistical tests employed a dependent t-test, independent t-test, and multiple linear regression test. This study revealed that the intervention group showed different cognitive function average values before and after implementing the exercise programs (p-value = 0.001). In contrast, the control group did not show any differences. The intervention and control groups showed different cognitive function mean values after applying the exercise program (p-value = 0.057). Another finding denoted that the length of stay in the nursing home affected the elderly's cognitive functions). This research recommends policymakers and healthcare personnel use the developed exercise program to perform complementary therapy, empower the elderly, and be replaced by many orders of the healthcare system.